Quality assurance method for monitoring of lateral pencil beam positions in scanned carbon-ion radiotherapy using tracking of secondary ions - Félix-Bautista, Renato; Ghesquière-Diérickx, Laura; Marek, Lukáš; Granja, Carlos; Soukup, Pavel; Turecek, Daniel; Kelleter, Laurent; Brons, Stephan; Ellerbrock, Malte; Jäkel, Oliver; Gehrke, Tim; Martišíková, Mária (Medical physics, 2021)
PURPOSE: Ion beam radiotherapy offers enhances dose conformity to the tumor volume while better sparing healthy tissue compared to conventional photon radiotherapy. However, the increased dose gradient also makes it more sensitive to uncertainties. While the most important uncertainty source is the patient itself, the beam delivery is also subject to uncertainties. Most of the proton therapy centers used cyclotrons, which deliver typically a stable beam over time, allowing a continuous extraction of the beam. Carbon-ion beam radiotherapy (CIRT) in contrast uses synchrotrons and requires a larger and energy-dependent extrapolation of the nozzle-measured positions to obtain the lateral beam positions in the isocenter, since the nozzle-to-isocenter distance is larger than for cyclotrons. Hence, the control of lateral pencil beam positions at isocenter in CIRT is more sensitive to uncertainties than in proton radiotherapy. Therefore, an independent monitoring of the actual lateral positions close to the isocenter would be very valuable and provide additional information. However, techniques capable to do so are scarce, and they are limited in precision, accuracy and effectivity. METHODS: The detection of secondary ions (charged nuclear fragments) has previously been exploited for the Bragg peak position of C-ion beams. In our previous work, we investigated for the first time the feasibility of lateral position monitoring of pencil beams in CIRT. However, the reported precision and accuracy were not sufficient for a potential implementation into clinical practice. In this work, it is shown how the performance of the method is improved to the point of clinical relevance. To minimize the observed uncertainties, a mini-tracker based on hybrid silicon pixel detectors was repositioned downstream of an anthropomorphic head phantom. However, the secondary-ion fluence rate in the mini-tracker rises up to 1.5 × 105 ions/s/cm2 , causing strong pile-up of secondary-ion signals. To solve this problem, we performed hardware changes, optimized the detector settings, adjusted the setup geometry and developed new algorithms to resolve ambiguities in the track reconstruction. The performance of the method was studied on two treatment plans delivered with a realistic dose of 3 Gy (RBE) and averaged dose rate of 0.27 Gy/s at the Heidelberg Ion-Beam Therapy Center (HIT) in Germany. The measured lateral positions were compared to reference beam positions obtained either from the beam nozzle or from a multi-wire proportional chamber positioned at the room isocenter. RESULTS: The presented method is capable to simultaneously monitor both lateral pencil beam coordinates over the entire tumor volume during the treatment delivery, using only a 2-cm2 mini-tracker. The effectivity (defined as the fraction of analyzed pencil beams) was 100%. The reached precision of (0.6 to 1.5) mm and accuracy of (0.5 to 1.2) mm are in line with the clinically accepted uncertainty for QA measurements of the lateral pencil beam positions. CONCLUSIONS: It was demonstrated that the performance of the method for a non-invasive lateral position monitoring of pencil beams is sufficient for a potential clinical implementation. The next step is to evaluate the method clinically in a group of patients in a future observational clinical study.
Keywords: Humans; metoda Monte Carlo; Carbon; celková dávka radioterapie; Monte Carlo Method; Proton Therapy; protonová terapie; uhlík; plánování radioterapie pomocí počítače; Heavy Ion Radiotherapy; Radiotherapy Dosage; radioterapie těžkými ionty; lidé; ionty; Ions; Radiotherapy Planning, Computer-Assisted